Performance analysis of peak signal-to-noise ratio and multipath source routing using different denoising method - Kannadhasan Suriyan; Nagarajan Ramaingam; Sudarmani Rajagopal; Jeevitha Sakkarai; Balakumar Asokan; Manjunathan Alagarsamy (Bulletin of Electrical Engineering and Informatics, 2022)
The problem of denoising iris pictures for iris identification systems will be discussed, as well as a novel solution based on wavelet and median filters. Different salt and pepper extraction algorithms, as well as Gaussian and speckle noises, were used. Because diverse sounds decrease picture quality during image collection, noise reduction is even more important. To reduce sounds like salt and pepper, Gaussian, and speckle, filtering (median, wiener, bilateral, and Gaussian) and wavelet transform are utilised. Provide better results as compared to other ways. A study of several efficiency indicators such as peak signal-to-noise ratio (PSNR) and mean squared error will be used to demonstrate the superiority of the proposed technique (MSE).